MODEL SMART CONTRACT BERBASIS BLOCKCHAIN UNTUK OTOMATISASI PENGADAAN DAN PEMBAYARAN MATERIAL KONSTRUKSI - Taimur Ahmad Yuda; Tri Joko Wahyu Adi; Yusroniya Eka Putri Rachman Waliulu; Muhammad Asyrofi Al Hakim (LPPM Universitas Abdurrab, 2026)
Material procurement in construction projects is a complex process involving multiple stakeholders. However, this critical process is not yet supported by an adequate system. Most procurement activities in construction are still conducted manually and have not been digitized, resulting in limited real-time visibility, weak data exchange mechanisms between parties, and a lack of information security assurance. Furthermore, the staged payment schemes commonly used in construction often disrupt cash flow within the supply chain. These issues can lead to conflicts among stakeholders and project delays. Therefore, this study proposes a solution by developing a blockchain-based smart contract model to automate the procurement and payment processes of construction materials in a more transparent, secure, and efficient manner. The methods employed include the development of smart contract procedures, the creation of a blockchain network, and simulations within a blockchain environment using Project X as a case study. Validation was then carried out to assess the time efficiency gained compared to traditional procurement methods as a result of implementing the blockchain-based model. The results show that the blockchain-based smart contract model can improve procurement time efficiency by approximately 78% to 83%, primarily by reducing the duration of administrative and payment processes.